PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA - Eneng Resti; Riska Wandini; Rilyani Rilyani (JKM (Jurnal Kebidanan Malahayati), 2021)
SUPPLYING ASI (MP-ASI) COMPLEMENTARY FOOD ASSOCIATED WITH STUNTING EVENTS IN BABIES Background: The prevalence of children under five with stunting in Indonesia in 2017 (36.4%) according to the 2018 Basic Health Research Lampung, which was ranked 24th out of 32 provinces in Indonesia, namely 27.3% with the highest incidence in Way Kanan (36.07%) being the lowest are in Metro City (14.75%). One of the factors causing stunting is the provision of complementary feeding (MP-ASI) which is not fulfilled in terms of time, frequency and type of food given to toddlers.Purpose: To knowing the relationship between complementary feeding (MP-ASI) and the incidence of stunting in mothers who have the characteristics of children aged 7-24 months at Public Health Services (Puskesmas) Hanura Teluk Pandan Pesawaran Regency 2020.Methods: This type of quantitative research used a cross sectional design and the population of this study were mothers who had children aged 7-24 months in the Hanura Public Health Center with 41 respondents using total sampling technique. The instrument in this study used a questionnaire sheet and the determination of stunting by calculating the Z-Score PB / U <-2SD, bivariate analysis using the Chi-Square test.Results: The statistical test of complementary feeding (MP-ASI) Chi-Square obtained P-Value = 0.000 with an Odd Ratio value of 0.083.Conclusion: There is a relationship between complementary feeding (MP-ASI) with the incidence of stunting in children under five at the working area of Public Health Services (Puskesmas) Hanura Teluk Pandan District, Pesawaran Regency in 2020. Suggestions will further improve the community outreach program, especially for mothers who have a toddler to prevent stunting in the future. Keywords : Stunting, complementary feeding, toddlers ABSTRAK Pendahuluan: Prevalensi balita stunting di Indonesia pada tahun 2018 adalah 30,8% menurut Riset Dasar Kesehatan tahun 2018 Lampung menjadi peringkat ke-24 dari 32 provinsi di Indonesia yaitu 27,3% dengan kejadian tertinggi di Way Kanan 36,07% sedang yang terendah terdapat di Kota Metro 14,75%. Salah satu faktor penyebab stunting adalah pemberian makanan pendamping ASI (MP-ASI) yang tidak terpenuhi baik dari waktu, frekuensi serta jenis makanan yang diberikan kepada balita.Tujuan: Untuk mengetahui hubungan pemberian makanan pendamping ASI (MP-ASI) dengan kejadian stunting pada ibu yang memiliki karakteristik balita usia 7-24 bulan di wilayah kerja Puskesmas Hanura Kecamatan Teluk Pandan Kabupaten Pesawaran Tahun 2020.Metode: Jenis penelitian kuantitatif dengan menggunakan rancangan cross sectional dan populasi dari penelitian ini yaitu ibu yang memiliki balita usia 7-24 bulan di wilayah kerja Puskesmas Hanura dengan jumlah responden 41 orang dengan teknik total sampling. Instrumen dalam penelitian ini dengan menggunakan lembar kuesioner dan penentuan stunting dengan perhitungan Z-Score PB/U <-2SD analisis bivariat dengan menggunakan uji Chi-Square.Hasil: Uji statistik pemberian makanan pendamping ASI (MP-ASI) Chi-Square didapat P-Value = 0.000 sehingga P-Value< α (0,000 <0,05) maka H0 ditolak dengan nilai Odd Ratio0.083.Kesimpulan: Terdapat hubungan pemberian makanan pendamping ASI (MP-ASI) dengan kejadian stunting pada balita di wilayah kerja Puskesmas Hanura Kecamatan Teluk Pandan Kabupaten Pesawaran Tahun 2020. Saran agar Puskesmas Hanura Kecamatan Teluk Pandan Kabupaten Pesawaran semakin meningkatkan program penyuluhan kepada masyarakat terutama pada ibu yang memiliki balita untuk mencegah terjadinya stunting dikemudian hari. Kata kunci   : Stunting, MP-ASI, Balita